The Effect of Dexamethasone Treatment to Humoral Immunity in BALB/C Mice Models - Ovi Ardiana; Muhaimin Rifa'i (Biotropika: Journal of Tropical Biology, 2015)
ABSTRACT Glucocorticoids (GCs) are a class of steroid hormones which regulate a variety of essential biological functions. The profound anti-inflammatory and immunosuppressive activity of synthetic GCs, combined with their power to induce lymphocyte apoptosis place them among the most commonly prescribed drugs worldwide. Endogenous GCs also exert a wide range of immunomodulatory activities, including the control of T cell homeostasis. Dexamethasone is kind of glucocorticoid which is used to control some deseases. The purpose of this experiment is to know the effect of dexamethasone on B220. There are three different doses of treatments applied: 0.0 mg/kg BW (control), 0.5 mg/kg BW, and 10 mg/kg BW.  Each treatment uses 6 mice (2 weeks old) with intraperitoneal injection. The treated mice were observed for 7 days and spleen cells were isolated for flow cytometric immunophenotyping . The data were analyzed by BD CellQuest and tested using One-way ANOVA (p<0,05) then Tukey’s test with SPSS 16.0 for Windows program. The result of this experiment showed that the dose of 0.5 mg/kg BW did not decrease B220 cell number significantly, but the dose of 10 mg/kg BW did. Keyword : B220, Dexamethasone, Glucocorticoids